Stability of Chimerism in Non-Obese Diabetic Mice Achieved By Rapid T Cell Depletion Is Associated With High Levels of Donor Cells Very Early After Transplant - Lin, Jiaxin; Chan, William F. N.; Boon, Louis; Anderson, Colin C. (Frontiers in Immunology, 2018)
Stable mixed hematopoietic chimerism is a robust method for inducing donor specific tolerance with the potential to prevent rejection of donor islets in recipients with autoimmune type-1 diabetes. However, with reduced intensity conditioning, fully allogeneic chimerism in a tolerance resistant autoimmune-prone NOD recipient has rarely been successful. In this setting, successful multilineage chimerism has required either partial MHC matching, mega doses of bone marrow, or conditioning approaches that are not currently clinically feasible. Irradiation free protocols with moderate bone marrow doses have not generated full tolerance; donor skin grafts were rejected. We tested whether more efficient recipient T cell depletion would generate a more robust tolerance. We show that a combination of donor specific transfusion (DST)-cyclophosphamide (CYP) and multiple T cell depleting antibodies could induce stable high levels of fully allogeneic chimerism in NOD recipients. Less effective T cell depletion was associated with instability of chimerism. Stable chimeras appeared fully donor specific tolerant, with clonal deletion of allospecific T cells and acceptance of donor skin grafts, while recovering substantial immunocompetence. The loss of chimerism months after transplant was significantly associated with a lower level of chimerism and donor T cells within the first two weeks after transplant. Thus, rapid and robust recipient T cell depletion allows for stable high-levels of fully allogeneic chimerism and robust donor specific tolerance in the stringent NOD model while using a clinically feasible protocol. In addition, these findings open the possibility of identifying recipients whose chimerism will later fail, stratifying patients for early intervention.